Optimization control of all-terrain rescue lift vehicle safety performance based on state feedback - Jian Yao; Weiyu Qu; Dongmei Tian; Jimao Shi; Jiayun Wang; Baiyou Xu; Shouyi Wang (PLoS ONE, 2025)
The all-terrain rescue lift vehicle is instrumental in mining emergency rescue operations, with its operational stability being of utmost importance. This study focuses on the XZJ5240JQZ30 all-terrain rescue lift vehicle, optimizing its vehicle structure and steering system. A linear 2DOF model and a PID gain model were developed based on actual vehicle parameters. A feedback system was employed to adjust the rear-wheel steering angle, enabling four-wheel steering (4WS) vehicle control. Numerical simulations were conducted using TruckSim and Simulink software. Utilizing the classic Double lane-change scenario as a test scenario, the study compared variations in the vehicle's centroid slip angle and yaw rate at different speeds, analyzing the impact of PID gain on steering stability. Moreover, the relationship between the centroid height and 4WS vehicle stability at low speeds was examined. Based on these findings, practical application tests were performed on the XZJ5240JQZ30 all-terrain rescue lift vehicle, obtaining relevant data on steering angle error. The results indicate that vehicles equipped with the PID-optimized control system demonstrate significantly higher steering stability than those without it. Furthermore, in practical applications, the actual steering angle closely aligns with the theoretical values. This demonstrates that the proposed optimized control system has substantial practical application value.